A Supramolecular Antibiotic Switch for Plug‐and‐Play Antibacterial Regulation. Issue 5 (25th March 2022) - Xu, Shi‐Yuan; Peng, Zi‐Ze; Wang, Zi‐Xin; Li, Wen‐Zhen; Ye, Yu‐Yuan; Lin, Xiao‐Wei; Ruan, Yi‐Ru; Xiao, Ju; Li, Lingling; Wang, Wenjing; Wang, Xiao‐Qiang
Abstract: Constructing novel antibiotic switches is of great importance to fighting bacterial infections and reducing the public health threat caused by antibiotic abuse. In this work, a plug‐and‐play antibiotic switch based on the host‐guest interaction between berberine hydrochloride (BBR) and cucurbit[7]uril (CB[7]) is reported. BBR can be encapsulated in the cavity of CB[7] to form BBR@CB[7] with enhanced fluorescent emission and reduced antibacterial activity. And BBR can be released from BBR@CB[7] in the presence of other competitors, such as amantadine hydrochloride (ADA). The self‐assemble and disassemble ability of the supramolecular complex can be applied as facile plug‐and‐play antibiotic switch to "turn‐on" and "turn‐off" its antibacterial activity on demand. This work provides a simple, rapid, and efficient strategy for antibacterial regulation through supramolecular chemistry. Abstract : A plug‐and‐play antibiotic switch was constructed by supramolecular self‐assembly to control the antibacterial activity of berberine hydrochloride (BBR).